Küçük Asya - Texier, Charles, 1802-1871. ([Ankara] [Ankara])
3 c. (1. c. 395 s., [5] s. kitap fihristi, [1] s., [15] s. resim ; 3. c. 289, 31 s. alfabetik fihrist, [2] s., 5 katlı harita, [34] s. resim)